2018
DOI: 10.1029/2018jb015515
|View full text |Cite
|
Sign up to set email alerts
|

Slip‐Deficit Rate Distribution Along the Nankai Trough, Southwest Japan, With Elastic Lithosphere and Viscoelastic Asthenosphere

Abstract: In southwest Japan, great earthquakes have occurred on the plate interface along the Nankai trough with a recurrence time of approximately 100 years. Most previous studies estimated slip deficits on the seismogenic zone from interseismic Global Navigation Satellite System (GNSS) velocity data assuming slip‐response functions for an elastic medium. The observed surface velocities, however, include effects of viscoelastic relaxation in the asthenosphere caused by slip motion associated with seismic cycles. If th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 49 publications
6
77
0
Order By: Relevance
“…By combination of a suitable 3-D model and onshore broadband network, we confirmed that seismic slips due to SVLFEs repeatedly occurred on or near the PHS boundary from 2004 to 2016. The centroid locations of SVLFEs are also correlated with the zone of relatively high slip deficit rate (e.g., Noda et al, 2017;Yokota et al, 2016). Detected low-velocity zones within the accretionary prism toes, which may be characterized by high pore fluid pressure, correlated with SVLFE activity in 2015 determined by DONET stations (Nakano et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…By combination of a suitable 3-D model and onshore broadband network, we confirmed that seismic slips due to SVLFEs repeatedly occurred on or near the PHS boundary from 2004 to 2016. The centroid locations of SVLFEs are also correlated with the zone of relatively high slip deficit rate (e.g., Noda et al, 2017;Yokota et al, 2016). Detected low-velocity zones within the accretionary prism toes, which may be characterized by high pore fluid pressure, correlated with SVLFE activity in 2015 determined by DONET stations (Nakano et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
“…Our CMT inversions also revealed a spatial relationship between the occurrence of SVLFEs and the slip deficit rate. The centroid locations of SVLFEs are also correlated with the zone of relatively high slip deficit rate (e.g., Noda et al, 2017;Yokota et al, 2016). We focused our attention on SVLFE activity in April 2016.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TAKEMURA ET AL. 11,836 (Noda et al, 2018), where it can be seen that SVLFEs mostly occur in regions with a shear stress change rate of 0-5 kPa/y. The SVLFEs off Cape Muroto are concentrated in regions with a negative shear stress change rate, but this activity area is adjacent to a stress accumulation peak (>10 kPa/y) off Cape Muroto.…”
Section: Geophysical Research Lettersmentioning
confidence: 99%
“…Slip‐deficit rate distribution and shear stress change at the depth of 10 km. (a) Slip‐deficit rate distribution at the plate interface along the Nankai Trough (Noda et al, ). The blue and red color scales show slip‐deficit and slip‐excess rates at intervals of 20 mm/year, respectively.…”
Section: Shear Strain Energy Change Due To the Interplate Locking Alomentioning
confidence: 99%